Increasing specialist intensity at weekends to improve outcomes for patients undergoing emergency hospital admission: the HiSLAC two-phase mixed-methods study - Julian Bion; Cassie Aldridge; Chris Beet; Amunpreet Boyal; Yen-Fu Chen; Michael Clancy; Alan Girling; Timothy Hofer; Joanne Lord; Russell Mannion; Peter Rees; Chris Roseveare; et al. (National Institute for Health Research, 2021)
Background: NHS England's 7-day services policy comprised 10 standards to improve access to quality health care across all days of the week. Six standards targeted hospital specialists on the assumption that their absence caused the higher mortality associated with weekend hospital admission: the 'weekend effect'. The High-intensity Specialist-Led Acute Care (HiSLAC) collaboration investigated this using the implementation of 7-day services as a 'natural experiment'. Objectives: The objectives were to determine whether or not increasing specialist intensity at weekends improves outcomes for patients undergoing emergency hospital admission, and to explore mechanisms and cost-effectiveness. Design: This was a two-phase mixed-methods observational study. Year 1 focused on developing the methodology. Years 2-5 included longitudinal research using quantitative and qualitative methods, and health economics. Methods: A Bayesian systematic literature review from 2000 to 2017 quantified the weekend effect. Specialist intensity measured over 5 years used self-reported annual point prevalence surveys of all specialists in English acute hospital trusts, expressed as the weekend-to-weekday ratio of specialist hours per 10 emergency admissions. Hospital Episode Statistics from 2007 to 2018 provided trends in weekend-to-weekday mortality ratios. Mechanisms for the weekend effect were explored qualitatively through focus groups and on-site observations by qualitative researchers, and a two-epoch case record review across 20 trusts. Case-mix differences were examined in a single trust. Health economics modelling estimated costs and outcomes associated with increased specialist provision. Results: Of 141 acute trusts, 115 submitted data to the survey, and 20 contributed 4000 case records for review and participated in qualitative research (involving interviews, and observations using elements of an ethnographic approach). Emergency department attendances and admissions have increased every year, outstripping the increase in specialist numbers; numbers of beds and lengths of stay have decreased. The reduction in mortality has plateaued; the proportion of patients dying after discharge from hospital has increased. Specialist hours increased between 2012/13 and 2017/18. Weekend specialist intensity is half that of weekdays, but there is no relationship with admission mortality. Patients admitted on weekends are sicker (they have more comorbid disease and more of them require palliative care); adjustment for severity of acute illness annuls the weekend effect. In-hospital care processes are slightly more efficient at weekends; care quality (errors, adverse events, global quality) is as good at weekends as on weekdays and has improved with time. Qualitative researcher assessments of hospital weekend quality concurred with case record reviewers at trust level. General practitioner referrals at weekends are one-third of those during weekdays and have declined further with time. Limitations: Observational research, variable survey response rates and subjective assessments of care quality were compensated for by using a difference-in-difference analysis over time. Conclusions: Hospital care is improving. The weekend effect is associated with factors in the community that precede hospital admission. Post-discharge mortality is increasing. Policy-makers should focus their efforts on improving acute and emergency care on a 'whole-system' 7-day approach that integrates social, community and secondary health care. Future work: Future work should evaluate the role of doctors in hospital and community emergency care and investigate pathways to emergency admission and quality of care following hospital discharge. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 9, No. 13. See the NIHR Journals Library website for further project information.